Educational Managerial Competence and Pesantren Authority in Strengthening Literacy Awareness - Hafid; Imaniar Mahmuda; Ahmadi; Fitriatul Munawarah; Muhammad Ihsan Mahbub (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze and identify the managerial competencies of faculty members in fostering literacy awareness at Nurul Falah Jember. This study employs a qualitative design with a descriptive-exploratory approach. Data collection techniques include in-depth interviews, participatory observation, and document analysis. The data were then analyzed through the stages of data reduction, data presentation, and drawing conclusions, using techniques to ensure data validity, credibility, triangulation of methods and sources, and confirmability. Based on the research findings, it was concluded that teachers at the Nurul Falah Islamic Boarding School in Jember fulfill their roles as authority figures by designing programs, organizing literacy teams, motivating teaching staff and other personnel, optimizing the boarding school’s resources, and overseeing activities through monitoring the progress of activities and the achievement of literacy program goals, while utilizing the results of this monitoring to improve the quality of student learning through a sustainable literacy program.